2011
DOI: 10.1007/s00339-011-6372-6
|View full text |Cite
|
Sign up to set email alerts
|

Indium tin oxide nanowires growth by dc sputtering

Abstract: Indium tin oxide nanowires have been grown by dc sputtering on different substrates without the use of catalysts or oblique deposition. The nanowire length was of the order of several µm, while their diameter was ∼50-100 nm. Small side branches on the nanowires were frequently observed. The nanowires were characterized by scanning electron microscopy, transmission electron microscopy, and X-ray diffraction. The growth mechanism of the nanowires is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…Especially in nanoscale region, the Sn-doped In 2 O 3 (ITO) nanowires have exhibited some superior properties such as good thermal stability, higher metallic conductivity, and excellent oxidation resistance, which make ITO nanowires (NWs) being suitable as a promising candidate not only as a transparent electrode but also as an emitter [4-7]. Up to now, several research groups have reported the growth of ITO nanowires, nanorods, and nanowhisker with different synthetic methods, such as thermal evaporation [8-11], electron beam evaporation [12], sputtering [13], and pulse laser deposition [14]. These nanostructures were found to exhibit a good performance at field emission as an electron emitter due to their high aspect ratio at the nanoscale region and unique extrinsic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in nanoscale region, the Sn-doped In 2 O 3 (ITO) nanowires have exhibited some superior properties such as good thermal stability, higher metallic conductivity, and excellent oxidation resistance, which make ITO nanowires (NWs) being suitable as a promising candidate not only as a transparent electrode but also as an emitter [4-7]. Up to now, several research groups have reported the growth of ITO nanowires, nanorods, and nanowhisker with different synthetic methods, such as thermal evaporation [8-11], electron beam evaporation [12], sputtering [13], and pulse laser deposition [14]. These nanostructures were found to exhibit a good performance at field emission as an electron emitter due to their high aspect ratio at the nanoscale region and unique extrinsic properties.…”
Section: Introductionmentioning
confidence: 99%
“…This can be achieved by different processes leading to various film morphologies. Recently, nanostructured ITO electrodes were obtained either chemically using sol-gel processes 4,5,8 and controlled self-assembly of nanoparticles, 14 or physically through the sintering of ITO nanoparticles coating, dc-sputtering 15 and by vacuum-based glancing-angle deposition (GLAD). 16 In most of these processes, metal oxide deposition is followed by annealing steps to improve the physical properties of the material, including stability, transparency and conductivity.…”
mentioning
confidence: 99%
“…These features make this material to be widely applied in optoelectronic devices, such as solar cells and liquid crystal displays [1,2]. The sputtering method is commonly used for ITO thin film deposition [3][4][5][6] and until the time of writing this paper, only two reports about the growth of ITO nanowires by sputtering have been published [7,8]. Oxide nanowire growth by sputtering usually follows the vapor-liquid-solid (VLS) mechanism.…”
Section: Introductionmentioning
confidence: 98%
“…According to this mechanism, the sputtered material dissolves in the molten droplets of a low melting point metal acting as a seed layer and precipitate at the interface between the droplet and the surface of the substrate [1]. Fung et al [7] obtained ITO nanostructures with different morphologies, including nanowires, by DC sputtering over different substrates. The depositions were conducted at high temperature (350 • C) in an atmosphere of Argon.…”
Section: Introductionmentioning
confidence: 98%